2016
DOI: 10.20473/j.djmkg.v49.i1.p1-4
|View full text |Cite
|
Sign up to set email alerts
|

Methisoprinol as an immunomodulator for treating infectious mononucleosis

Abstract: Background: Infectious mononucleosis (IM) is the self limiting disease that associated with primary Epstein Barr virus (EBV). It is a gamma herpes virus. EBV infection is follows saliva-transfer by kissing or sexual intercourse. The most clinical manifestation in IM consists mainly of the specific sign: pharyngitis, fever, and lymphadenopathy. The main therapy is supportive treatment. Actually the antiviral therapy is required for the host with high response immune. Purpose: The aimed of this study was to repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…It helps the body to fight infection and is recommended to be taken even though the condition has improved to avoid reinfection. 23 Adequate fluid intake may prevent dehydration from painful oral lesions. Cold liquids are usually preferred.…”
Section: Discussionmentioning
confidence: 99%
“…It helps the body to fight infection and is recommended to be taken even though the condition has improved to avoid reinfection. 23 Adequate fluid intake may prevent dehydration from painful oral lesions. Cold liquids are usually preferred.…”
Section: Discussionmentioning
confidence: 99%
“…Methisoprinol can be prescribed during the onset of the disease as a prophylaxis against reactivation of latent Varicella zoster infection. 12,14 The etiology of HFMD is Enterovirus 71 or Coxsackie virus, both of which constitute RNA viruses. The case reported here indicated that HFMD can be treated with methisoprinol which contains an antiviral and immunomodulator agent, as opposed to acyclovir, because HFMD is not a herpes virus.…”
Section: Discussionmentioning
confidence: 99%
“…It can modulate T-lymphocyte and natural killer cell cytotoxicity, T4 helper and T8 suppressor cell functions. 14,15 Based on the foregoing discussion, it can be concluded that a dentist is responsible for detecting specific clinical symptoms of a disease to distinguish HFMD and Primary varicella zoster infection. Although these diseases share similar clinical symptoms, they have contrasting etiologies which require different treatment.…”
Section: Discussionmentioning
confidence: 99%
“…He was prescribed acyclovir which can prevent virus replication through three mechanisms: phosphorylation of acyclovir to phosphate derivates within the cell via viral thymidine kinase, inhibition of DNA polymerase by acyclovir activation, and termination of chain elongation by eliminating cyclic sugar from acyclovir triphosphate. 12 Acceleration of the wound healing process and prevention of secondary infection in herpes labialis were managed by prescribing topical alloclair to be gargled and topical application to the lower lip region. Due to its aloevera extract content, aloclair can accelerate wound healing through stimulation of and increase in anti-inflammatory cell activity which enhances the reepithelization process.…”
Section: Discussionmentioning
confidence: 99%